Peran Penting Keimigrasian dalam Masalah Penyeludupan Manusia dan Perdagangan Orang - Arsyad Imam Baihaqi; Endra Inggita Sabriyartendra; Salsabila Putri Salam (Universitas Batanghari Jambi, 2021)
The crime of human trafficking is still a major topic in world discussion as well as the most striking point of attention because of the seriousness of the problem. Trafficking in persons is a major problem of modern globalization because the existence of this crime has already become an epidemic in many countries. This research aim to find out how the process of People Smuggling and Trafficking in Indonesia occurs, the legal basis and enforcement of the crime of people smuggling and trafficking. As well as the Accountability Process for the perpetrators of the Crime of Smuggling and Human Trafficking. By using descriptive research method is the method used in this study, this method has the aim of describing things that are currently in effect, including efforts to describe something or describe, record, analyze and explain current (actual) conditions. And the results will be obtained, namely the crime of human trafficking, the perpetrators use various ways to smooth the crime. Furthermore, the Rules regarding Human Smuggling and Trafficking in Persons in Indonesia are contained in several laws and regulations, namely Law Number 6 of 2011, concerning Immigration. Then in criminal liability, people who commit criminal acts of people smuggling and human trafficking are based on the provisions of Law no. 6 of 2011 concerning Immigration.